Application of Kangaroo Mother Care (KMC) Method to Maintain Body Temperature Stability of Low Birth Weight (LBW) Babies at Toto Kabila Gorontalo Hospital - Apriana, Rista; Syahrir, Akifa; Sunge, Grace Wellyana (Fakultas Kedokteran, 2023)
Background: LBW infants are infants born with a weight of less than 2500 grams. Due to their larger surface area-to-body weight ratio, they are highly susceptible to thermoregulation system disturbances, such as hypothermia. One non-pharmacological intervention to maintain body temperature in infants is the Kangaroo Mother Care (KMC) method, as it helps stabilize heart rate and respiration and reduces the risk of infections in infants. Aim: To describe the results of applying the KMC method to LBW infants at RSUD Toto Kabila Regional Public Hospital. Method: The study design used is a descriptive case study involving three participants. The data will be presented using tables and described to illustrate the results and describe the application of the KMC method on LBW infants. Result: All three respondents experienced different increases in body temperature after applying the KMC method. The highest temperature increase was 1.9°C, while the lowest temperature increase was 1°C. Conclusion: The application of the KMC method was able to maintain normal body temperature stability, as demonstrated by the pre- and post-measurement results of body temperature after three days of applying the method on three LBW infants at RSUD Toto Kabila Regional Public Hospital.Keywords: LBW Kangaroo Mother Care, Body Temperature Stability